Corrosion-resistant inorganic silicon crystal-based nano enhanced coating and preparation method thereof
By using corrosion-resistant inorganic silicon crystal-based nanoreinforced coatings in the coatings, combined with modified epoxy resin and nanosilicon dioxide, the shortcomings of existing coatings in terms of corrosion resistance, chemical stability and thermal stability are solved, and higher coating performance and service life are achieved.
Patent Information
- Application Number
- CN202411822480.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-15
AI Technical Summary
The performance of existing coatings in terms of corrosion resistance, chemical stability and thermal stability affects the service life of the coating.
Corrosion-resistant inorganic silicon crystal-based nano-reinforced coatings are used, and their components include epoxy resin, polytetrafluoroethylene, nanosilica, fluorosiloxane, styrene acrylic emulsion, polyurethane prepolymer, acrylic acid, butyl acetate, defoaming agent, polyvinyl alcohol, phosphorus-containing monomer and catalyst. By modifying the epoxy resin and nanosilica, a coating with excellent chemical stability and thermal stability is formed.
It improves the chemical stability, thermal stability and corrosion resistance of the coating and extends the service life of the coating.
Smart Images

Figure BDA0005183412600000051 
Figure BDA0005183412600000061 
Figure BDA0005183412600000062
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a corrosion-resistant inorganic silicon crystal-based nano-enhanced coating and a preparation method thereof. Background Art
[0002] Paint, traditionally known as varnish in China, is a viscous liquid that is applied to the surface of an object to be protected or decorated and can form a firmly attached continuous film with the coated object. It is usually based on resin, oil, or emulsion, with or without pigments and fillers, and with corresponding additives, and is prepared with organic solvents or water.
[0003] A Chinese patent with announcement number CN104059526B discloses an antioxidant non-stick coating for tableware, the raw materials of which are as follows: component A is 35-45%, component B is 20-30%, filler is 1-3%, and isopropyl alcohol is the balance; the component A is alkyl siloxane, the component B is a mixture of β-heptamethyltrisiloxane-ethyltrimethoxysilane and nano silver particles, and the molar ratio of the two is 1:0.2; the filler is one or a mixture of silica whiskers, alumina whiskers, nano-precipitated barium sulfate, and potassium tetratitanate whiskers.
[0004] Although the coating disclosed in the above technology has certain high temperature resistance, its performance in corrosion resistance, chemical stability and thermal stability needs to be improved, which is not conducive to improving the service life of the coating. Therefore, it is necessary to improve the coating in the relevant technology. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a corrosion-resistant inorganic silicon crystal-based nano-enhanced coating and a preparation method thereof. The corrosion-resistant inorganic silicon crystal-based nano-enhanced coating has good chemical stability, thermal stability and corrosion resistance.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0007] A corrosion-resistant inorganic silicon crystal-based nano-enhanced coating comprises the following raw materials in parts by weight: 30-40 parts of epoxy resin, 4-8 parts of polytetrafluoroethylene, 30-40 parts of nano-silicon dioxide, 5-15 parts of fluorine-containing silicone, 40-50 parts of styrene-acrylic emulsion, 10-20 parts of polyurethane prepolymer, 10-20 parts of acrylic acid, 5-15 parts of butyl acetate, 1-5 parts of defoaming agent, 10-20 parts of polyvinyl alcohol, 10-20 parts of phosphorus-containing monomer and 1-5 parts of catalyst.
[0008] Preferably, the coating comprises the following raw materials in parts by weight: 35 parts of epoxy resin, 6 parts of polytetrafluoroethylene, 35 parts of nano-silicon dioxide, 10 parts of fluorinated silicone, 45 parts of styrene-acrylic emulsion, 15 parts of polyurethane prepolymer, 15 parts of acrylic acid, 10 parts of butyl acetate, 3 parts of defoaming agent, 15 parts of polyvinyl alcohol, 15 parts of phosphorus-containing monomer and 3 parts of catalyst.
[0009] The present invention also discloses a method for preparing a corrosion-resistant inorganic silicon crystal-based nano-enhanced coating, which comprises the following steps:
[0010] S1. Preparation of modified epoxy resin;
[0011] S2, preparation of modified nano-silica;
[0012] S3, weighing the styrene-acrylic emulsion according to the proportion, adding it together with the modified nano-silica obtained in step S2 into a single-necked flask, stirring and ultrasonically treating at room temperature for 15 minutes, and setting aside;
[0013] S4, weigh the remaining materials in proportion, mix them with the modified epoxy resin obtained in step S1 and the materials obtained in step S3, stir them evenly, and adjust the pH of the system to 5-6 to obtain the corrosion-resistant inorganic silicon crystal-based nano-enhanced coating.
[0014] Preferably, the preparation steps of the modified epoxy resin are: epoxy resin, catalyst and acrylic acid are weighed in proportion and added into a round-bottom flask, and stirred at 400-500 r / min for 10-20 min at 80-90° C.
[0015] Preferably, the preparation steps of modified nano-silica are: weigh nano-silica in proportion, weigh 95% ethanol solution in a mass ratio of 1:15, add them together into a three-necked flask, stir for 10-20 minutes at room temperature, then weigh fluorinated silicone in proportion and add it, adjust the pH to 5-6, dry after magnetic stirring, and crush to obtain nano-silica.
[0016] Preferably, the temperature of magnetic stirring is 70°C, the stirring time is 4.0h, and the drying temperature is 100°C.
[0017] Preferably, the phosphorus-containing monomer is one or more of dichlorophenyl phosphate, bisphenol S, allyl alcohol, 2-hydroxyethyl acrylate, 9,10-dihydro-9-oxa-10-phosphorylphenanthrene, bisphenol A, hydroquinone, 4,4′-difluorobenzophenone, diethyl phosphite, diallylaminomethyl diethyl phosphate or quaternary phosphonium salt tetrakis hydroxymethyl phosphonium sulfate; the catalyst is ferric chloride or pyridine.
[0018] Preferably, the epoxy resin is one of bisphenol A epoxy resin, glycidyl ether epoxy resin, glycidyl amine epoxy resin, alicyclic epoxy resin, water-based epoxy resin or aliphatic epoxy resin.
[0019] The beneficial effects of the present invention are:
[0020] The hydroxyl group in acrylic acid reacts with the carboxyl group in epoxy resin under the action of a catalyst to form an ester bond, which improves the toughness of the system. The modified epoxy resin is used to prepare the coating, which improves the toughness and wear resistance of the coating.
[0021] Fluorosiloxane is used to modify nano-silica to form a densely cross-linked hydrophobic layer on the surface of the silica, thereby improving the waterproof performance, stain resistance and scrub resistance of the coating.
[0022] Polytetrafluoroethylene is a plastic material with extremely high inertness, chemical corrosion resistance and high temperature resistance. It has excellent chemical stability and thermal stability and can be used for a long time in high temperature and chemical corrosion environments.
[0023] The addition of phosphorus-containing monomers makes the coating have good flame retardancy, chemical resistance and weather resistance. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] A corrosion-resistant inorganic silicon crystal-based nano-enhanced coating comprises the following raw materials in parts by weight: 30-40 parts of epoxy resin, 4-8 parts of polytetrafluoroethylene, 30-40 parts of nano-silicon dioxide, 5-15 parts of fluorine-containing silicone, 40-50 parts of styrene-acrylic emulsion, 10-20 parts of polyurethane prepolymer, 10-20 parts of acrylic acid, 5-15 parts of butyl acetate, 1-5 parts of defoaming agent, 10-20 parts of polyvinyl alcohol, 10-20 parts of phosphorus-containing monomer and 1-5 parts of catalyst.
[0026] The phosphorus-containing monomer is one or more of dichlorophenyl phosphate, bisphenol S, allyl alcohol, 2-hydroxyethyl acrylate, 9,10-dihydro-9-oxa-10-phosphorylphenanthrene, bisphenol A, hydroquinone, 4,4′-difluorobenzophenone, diethyl phosphite, diethyl diallylaminomethyl phosphate or quaternary phosphonium salt tetrakis hydroxymethyl phosphonium sulfate. The catalyst is ferric chloride or pyridine.
[0027] The epoxy resin is one of bisphenol A epoxy resin, glycidyl ether epoxy resin, glycidyl amine epoxy resin, alicyclic epoxy resin, water-based epoxy resin or aliphatic epoxy resin.
[0028] A method for preparing a corrosion-resistant inorganic silicon crystal-based nano-enhanced coating comprises the following steps: S1, preparation of modified epoxy resin: epoxy resin, catalyst, and acrylic acid are weighed in proportion and added into a round-bottom flask, and stirred at a speed of 400-500 r / min for 10-20 min at 80-90° C.;
[0029] S2. Preparation of modified nano-silica: weigh nano-silica in proportion, weigh 95% ethanol solution in a mass ratio of 1:15, add them together into a three-necked flask, stir for 10-20 minutes at room temperature, then weigh fluorinated siloxane in proportion and add, adjust the pH to 5-6, magnetically stir at 70°C for 4.0h, centrifuge, dry at 100°C, and crush to obtain nano-silica;
[0030] S3, weighing the styrene-acrylic emulsion according to the proportion, adding it together with the modified nano-silica obtained in step S2 into a single-necked flask, stirring and ultrasonically treating at room temperature for 15 minutes, and setting aside;
[0031] S4, weigh the remaining materials in proportion, mix them with the modified epoxy resin obtained in step S1 and the materials obtained in step S3, stir them evenly, and adjust the pH of the system to 5-6 to obtain the corrosion-resistant inorganic silicon crystal-based nano-enhanced coating.
[0032] Embodiment 1:
[0033] A corrosion-resistant inorganic silicon crystal-based nano-enhanced coating, the proportions of the raw material components in the coating are as follows:
[0034] Table 1 Ratio of each raw material component in Example 1
[0035] Components Weight / g Bisphenol A epoxy resin 30 Polytetrafluoroethylene 4 Nano Silica 30 Fluorosilicone 5 Styrene acrylic emulsion 40 Polyurethane prepolymer 10 acrylic acid 10 Butyl acetate 5 Defoaming agent 1 Polyvinyl alcohol 10 Phenyl dichloride phosphate 10 Ferric chloride 1
[0036] Embodiment 2:
[0037] A corrosion-resistant inorganic silicon crystal-based nano-enhanced coating, the proportions of the raw material components in the coating are as follows:
[0038] Table 2 Ratio of each raw material component in Example 2
[0039]
[0040]
[0041] Embodiment 3:
[0042] A corrosion-resistant inorganic silicon crystal-based nano-enhanced coating, the proportions of the raw material components in the coating are as follows:
[0043] Table 3 Ratio of each raw material component in Example 3
[0044]
[0045] Embodiment 4:
[0046] A corrosion-resistant inorganic silicon crystal-based nano-enhanced coating, the proportions of the raw material components in the coating are as follows:
[0047] Table 4 Ratio of each raw material component in Example 4
[0048]
[0049]
[0050] Embodiment 5:
[0051] A corrosion-resistant inorganic silicon crystal-based nano-enhanced coating, the proportions of the raw material components in the coating are as follows:
[0052] Table 5 Ratios of the raw material components in Example 5
[0053]
[0054]
[0055] Comparative Example 1:
[0056] A corrosion-resistant inorganic silicon crystal-based nano-enhanced coating. The corrosion-resistant inorganic silicon crystal-based nano-enhanced coating is different from Example 3 only in that polytetrafluoroethylene is not added.
[0057] Comparative Example 2:
[0058] A corrosion-resistant inorganic silicon crystal-based nano-enhanced coating. The corrosion-resistant inorganic silicon crystal-based nano-enhanced coating is different from Example 3 only in that no fluorinated siloxane is added.
[0059] Comparative Example 3:
[0060] A corrosion-resistant inorganic silicon crystal-based nano-enhanced coating. The corrosion-resistant inorganic silicon crystal-based nano-enhanced coating is different from Example 3 only in that no styrene acrylic emulsion is added.
[0061] Comparative Example 4:
[0062] A corrosion-resistant inorganic silicon crystal-based nano-enhanced coating. The corrosion-resistant inorganic silicon crystal-based nano-enhanced coating is different from Example 3 only in that no polyurethane prepolymer is added.
[0063] Comparative Example 5:
[0064] A corrosion-resistant inorganic silicon crystal-based nano-enhanced coating. The corrosion-resistant inorganic silicon crystal-based nano-enhanced coating is different from Example 3 only in that no acrylic acid is added.
[0065] Comparative Example 6:
[0066] A corrosion-resistant inorganic silicon crystal-based nano-enhanced coating. The corrosion-resistant inorganic silicon crystal-based nano-enhanced coating is different from Example 3 only in that butyl acetate is not added.
[0067] Comparative Example 7:
[0068] A corrosion-resistant inorganic silicon crystal-based nano-enhanced coating. The corrosion-resistant inorganic silicon crystal-based nano-enhanced coating is different from Example 3 only in that polyvinyl alcohol is not added.
[0069] Comparative Example 8:
[0070] A corrosion-resistant inorganic silicon crystal-based nano-enhanced coating. The corrosion-resistant inorganic silicon crystal-based nano-enhanced coating is different from Example 3 only in that no allyl alcohol is added.
[0071] Comparative Example 9:
[0072] A corrosion-resistant inorganic silicon crystal-based nano-enhanced coating. The corrosion-resistant inorganic silicon crystal-based nano-enhanced coating is different from Example 3 only in that ferric chloride is not added.
[0073] The coatings obtained in the above Examples 1-5 and Comparative Examples 1-9 were subjected to performance tests to measure the comprehensive performance of the coatings. The results are shown in Table 6.
[0074] Table 6 Performance parameters of the coatings obtained in Examples 1-5 and Comparative Examples 1-9
[0075]
[0076] From Table 6, we can see that:
[0077] No addition of polytetrafluoroethylene, fluorosilicone, or polyurethane prepolymer has a significant impact on the corrosion resistance of the coating. No addition of fluorosilicone and acrylic acid has a significant impact on the toughness of the coating. No addition of polytetrafluoroethylene and polyurethane prepolymer has a significant impact on the toughness of the coating.
[0078] In summary:
[0079] The hydroxyl group in acrylic acid reacts with the carboxyl group in epoxy resin under the action of a catalyst to form an ester bond, which improves the toughness of the system. The modified epoxy resin is used to prepare the coating, which improves the toughness and wear resistance of the coating.
[0080] Fluorosiloxane is used to modify nano-silica to form a densely cross-linked hydrophobic layer on the surface of the silica, thereby improving the waterproof performance, stain resistance and scrub resistance of the coating.
[0081] Polytetrafluoroethylene is a plastic material with extremely high inertness, chemical corrosion resistance and high temperature resistance. It has excellent chemical stability and thermal stability and can be used for a long time in high temperature and chemical corrosion environments.
[0082] The addition of phosphorus-containing monomers makes the coating have good flame retardancy, chemical resistance and weather resistance.
[0083] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A corrosion-resistant inorganic silicon crystal-based nano-enhanced coating, characterized in that: The coating comprises the following raw materials in parts by weight: 30-40 parts of epoxy resin, 4-8 parts of polytetrafluoroethylene, 30-40 parts of nano silicon dioxide, 5-15 parts of fluorine-containing silicone, 40-50 parts of styrene-acrylic emulsion, 10-20 parts of polyurethane prepolymer, 10-20 parts of acrylic acid, 5-15 parts of butyl acetate, 1-5 parts of defoaming agent, 10-20 parts of polyvinyl alcohol, 10-20 parts of phosphorus-containing monomer and 1-5 parts of catalyst.
2. The corrosion-resistant inorganic silicon crystal-based nano-enhanced coating according to claim 1, characterized in that: The coating comprises the following raw materials in parts by weight: 35 parts of epoxy resin, 6 parts of polytetrafluoroethylene, 35 parts of nano silicon dioxide, 10 parts of fluorine-containing silicone, 45 parts of styrene-acrylic emulsion, 15 parts of polyurethane prepolymer, 15 parts of acrylic acid, 10 parts of butyl acetate, 3 parts of defoaming agent, 15 parts of polyvinyl alcohol, 15 parts of phosphorus-containing monomer and 3 parts of catalyst.
3. A method for preparing the corrosion-resistant inorganic silicon crystal-based nano-enhanced coating according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: S1. Preparation of modified epoxy resin; S2, preparation of modified nano-silica; S3, weighing the styrene-acrylic emulsion according to the proportion, adding it together with the modified nano-silica obtained in step S2 into a single-necked flask, stirring and ultrasonically treating at room temperature for 15 minutes, and setting aside; S4, weigh the remaining materials in proportion, mix them with the modified epoxy resin obtained in step S1 and the materials obtained in step S3, stir them evenly, and adjust the pH of the system to 5-6 to obtain the corrosion-resistant inorganic silicon crystal-based nano-enhanced coating.
4. The method for preparing the corrosion-resistant inorganic silicon crystal-based nano-enhanced coating according to claim 3, characterized in that: The preparation steps of modified epoxy resin are: Weigh epoxy resin, catalyst and acrylic acid in proportion and add them into a round-bottom flask. Stir at 400-500 r / min for 10-20 min at 80-90°C.
5. The method for preparing the corrosion-resistant inorganic silicon crystal-based nano-enhanced coating according to claim 3, characterized in that: The preparation steps of modified nano-silica are: Weigh nano-silicon dioxide in proportion, weigh 95% ethanol solution in a mass ratio of 1:15, add them into a three-necked flask, stir for 10-20 minutes at room temperature, then weigh fluorinated silicone in proportion and add, adjust the pH to 5-6, dry after magnetic stirring, and crush to obtain nano-silicon dioxide.
6. The method for preparing the corrosion-resistant inorganic silicon crystal-based nano-enhanced coating according to claim 5, characterized in that: The temperature of magnetic stirring was 70°C, the stirring time was 4.0 h, and the drying temperature was 100°C.
7. The method for preparing the corrosion-resistant inorganic silicon crystal-based nano-enhanced coating according to claim 6, characterized in that: The phosphorus-containing monomer is one or more of dichlorophenyl phosphate, bisphenol S, allyl alcohol, 2-hydroxyethyl acrylate, 9,10-dihydro-9-oxa-10-phosphorylphenanthrene, bisphenol A, hydroquinone, 4,4′-difluorobenzophenone, diethyl phosphite, diallylaminomethyl diethyl phosphate or quaternary phosphonium salt tetrakishydroxymethyl phosphonium sulfate; The catalyst is ferric chloride or pyridine.
8. The method for preparing the corrosion-resistant inorganic silicon crystal-based nano-enhanced coating according to claim 6, characterized in that: The epoxy resin is one of bisphenol A epoxy resin, glycidyl ether epoxy resin, glycidyl amine epoxy resin, alicyclic epoxy resin, water-based epoxy resin or aliphatic epoxy resin.
Citation Information
Patent Citations
A non-stick coating with antioxidant properties for tableware
CN104059526B